2020
DOI: 10.1089/biores.2020.0038
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Interference in Point of Care HIV Immunoassay

Abstract: The use of high concentrations of biotin as a dietary supplement to improve hair, skin, and nail quality has increased in the United States over the past few years. High concentrations of biotin have been shown to interfere with some diagnostic assays that use streptavidin-biotin interactions as one of the steps in the assay. The objective of this report is to evaluate potential biotin interference on the analytical and clinical sensitivity of a point of care (POC) antigen-antibody combo HIV-1 assay. We spiked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although a balanced nutritional diet provides sufficient biotin to support healthy and strong hair growth, the addition of biotin supplements is generally considered safe. Daily doses of more than 5,000 mcg do not provide additional benefits and can interfere with the results of diagnostic laboratory testing (Setty et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a balanced nutritional diet provides sufficient biotin to support healthy and strong hair growth, the addition of biotin supplements is generally considered safe. Daily doses of more than 5,000 mcg do not provide additional benefits and can interfere with the results of diagnostic laboratory testing (Setty et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the effect that biotin may have on laboratory tests, patients who have taken 5,000–10,000 mcg of biotin should wait 8–12 hr before having their blood collected for laboratory tests (Grimsey et al, 2017). If the patient is taking less than 5,000 mcg per day, this is not as much of a concern (Grimsey et al, 2017; Setty et al, 2020). Surprisingly, despite announcements from the FDA, approximately 1 in 5 physicians (19.5%) are unaware of the potential interference of biotin with laboratory results (Falotico & Lipner, 2022).…”
Section: Biotinmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Dengue NS1 can be cited as an example. Because false-positive results for this dengue biomarker have been reported in patients with acute zika infection, caution should be exercised when interpreting dengue NS1 results [ 182 ]. A group of researchers has shown that the combined use of Dengue NS1 and antibodies (IgM and IgG) improves diagnosis rates for dengue fever [ 183 , 184 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also an important marker of choice for predicting CD4 + [ 112 ]. However, it is also known that high concentrations of biotin prevent the detection of HIV-1 p24 antigen in serum [ 113 ]. This significantly reduces the specificity of the tests.…”
Section: Lfia Application Strategies For Infectious Disease Diagnosismentioning
confidence: 99%